Rhetoric to Alexander: text and intertexts - Jaskelevičius, Alius (Literatūra, 2023)
For a long time, Aristotle was considered the author of the “Rhetoric to Alexander”. However, in the 16th century, Anaximenes of Lampsacus came to be considered its author. Despite some links between the teachings of the “Rhetoric to Alexander” and those of Anaximenes, the question of authorship remains unresolved.Based on the text of the “Rhetoric to Alexander” that has come down to us, and in conjunction with other intertexts, attempts have been made to determine the extent to which the “Rhetoric to Alexander” may have been influenced by different authors and texts. This paper raises doubts about whether attributing the “Rhetoric to Alexander” to Anaximenes closes the debate on the authorship of this work.